ANALISIS RISIKO PENINGKATAN INFRASTRUKTUR JALAN RUAS ABEPURA-YETTI DENGAN PERSPEKTIF KONTRAKTOR DI JAYAPURA PAPUA - Asniaty Asniaty; Dewi Ana Rusim; Harmonis Rante (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2021)
Activities to improve road infrastructure in Jayapura Papua are growing. There are many risks faced by construction service companies in its implementation. One of them is the implementation of work to improve the road infrastructure for the Abepura-Yetti section. This study aims to identify the possible risks that occur in improving the road infrastructure for the Abepura-Yetti section and analyze the handling of the dominant risks in improving the AbepuraYetti road section. Data retrieval is carried out to contractors who are carrying out work. It is estimated that the risks that occur may hamper the completion of the road infrastructure improvement work for the Abepura-Yetti section. The indicator with the highest level of risk that affects cost performance and time performance on road infrastructure improvement for the Abepura-Yetti section is a late project related to land followed by unexpected land / location conditions and unexpected project location conditions.